(untitled) (Research Nepal Journal of Development Studies, 2019)
Wetlands despite being rich in biodiversity and associated ecosystem services, they are often poorly acknowledged by the concerned stakeholders. This lack of affirmation exposes wetlands to different anthropogenic disturbances, driving towards their loss and degradation. Population growth and enhanced purchasing power are exacerbating the problems. Non-consumptive value of wetlands for sustainable development are poorly explored in case of Nepal. This article aims to identify the prospects of ecotourism as tools for sustainable management of ecotourism in Nepal by synthesizing finding of available literatures on ecotourism and wetland. Nepal is home to 5000 lakes and many more wetlands but they are poorly managed and thus fail to make significant contribution to the local livelihood. Wise use of these valuable resources could turn wetlands into panacea. Ecotourism is one of the potential tool for wise use of wetlands. This sustainable alternative of mass tourism generates funds for conservation of wetland, generate economic opportunity and helps to address the issue of poverty and other social problems. Wetlands are home to wide variety of wild mammals, birds and other plants and animals thus are potential sites for ecotourism. Properly planned and executed ecotourism plans can this ecotourism potential into tools of sustainable development for Nepal.